Level Ib sparing intensity-modulated radiation therapy in selected nasopharyngeal carcinoma patients based on the International Guideline. (February 2022) - Guo, Qiaojuan; Xiao, Nan; Xu, Hanchuan; Zong, Jingfeng; Xiao, Youping; Lu, Tianzhu; Xu, Yun; Wang, Bingyi; Chen, Bijuan; Pan, Jianji; Lin, Shaojun
Highlights: Level Ib-sparing IMRT of the International Guideline merit further research. Sparing level Ib in patients with level II involvement with ECE may be feasible. Sparing level Ib in patients with a MAD of  ＞2 cm in level II may be feasible. Sparing level Ib in patients with negative pathological results of level Ib may be feasible. Abstract: Background and purpose: To investigate the feasibility of level Ib sparing in selected nasopharyngeal carcinoma (NPC) patients during intensity-modulated radiation therapy (IMRT) based on the International Guideline. Patients and materials: Patients with histologically-proven NPC who received definitive IMRT at our group were candidates for this analysis. Other eligibility criteria for analysis were designed according to the recommendation of International Guideline for selective coverage of level Ib. Survival outcomes focused on regional recurrence-free survival (RRFS) and level Ib recurrence rate were analyzed. Results: A total of 450 patients were included, 60 of them received level Ib-covering IMRT due to the first three principles of the International Guideline according to our protocol. Of note, patients with level Ib involvement would receive ultrasound guided puncture, only those with positive pathological results would undergo level Ib-covering IMRT. For the remaining 390 patients who only fulfilled the last two criteria and/or level Ib involvement with negative pathological results, level Ib-sparing IMRT was delivered, with a median follow-up time of 112 months (range 6 to 194 months), reported 5- and 10-year RRFS were 95.4% and 92.9%, respectively. Twenty-two patients occurred regional recurrence at censorship (median 44.5 months), only 4(4/390, 1.03%) were recorded as level Ib recurrence. Conclusion: Level Ib-sparing IMRT should be safe and feasible for patients who only had level II involvement with ECE, and/or had a MAD of greater than 2 cm in level II, and/or level Ib involvement with negative pathological results. Further well-designed multi-center prospective trials should be conducted.